2018
DOI: 10.1515/eng-2018-0032
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Lean Performance of Indian Small and Medium Sized Enterprises in Automotive Sector

Abstract: Under new “make in India policy” India has started to become global manufacturing hub and many Indian organizations are looking to implement lean philosophy to gain sustainable strategic benefits over others. Therefore, a need was felt to develop comprehensive lean evaluation system for Indian automotive small & medium sized enterprises in order to measure its present lean status and potential improvements to gain significant strategic advantages. Research started with the identification of various lean fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…Out of these 34 studies, 19 (65 percent) reported on a full implementation of lean practices (e.g. Dave and Sohani, 2019; Tiwari and Tiwari, 2018; Godinho Filho et al , 2016; Sharma et al , 2015). The remaining 12 (35 percent) studies reported on a partial implementation of lean practices in a developing economy.…”
Section: Literature Review Theoretical Background and Development Of Hypothesismentioning
confidence: 99%
“…Out of these 34 studies, 19 (65 percent) reported on a full implementation of lean practices (e.g. Dave and Sohani, 2019; Tiwari and Tiwari, 2018; Godinho Filho et al , 2016; Sharma et al , 2015). The remaining 12 (35 percent) studies reported on a partial implementation of lean practices in a developing economy.…”
Section: Literature Review Theoretical Background and Development Of Hypothesismentioning
confidence: 99%
“…The extant literature widely accepted that implementing improvement practices effectively led to better performance (e.g., quality performance) (Goncalves et al, 2019). However, Tiwari and Tiwari (2018) indicated several issues in adopting improvement practices related to employees' behaviour, such as resistance to change, lack of involvement, and lack of motivation.…”
Section: Discussion Limitations and Future Researchmentioning
confidence: 99%
“…With strong supervisory interaction facilitation to create a working environment where the employees perceive a safe and welcoming atmosphere for expressing their ideas for improvement, they are more likely to engage in process improvement programs (Stadnicka & Sakano, 2017;Tiwari & Tiwari, 2018). As a result, the manufacturing processes are quickly stabilised, and process variation is reduced, which is translated to the improvement of quality performance.…”
Section: Discussion Limitations and Future Researchmentioning
confidence: 99%
“…LPP requires a highly skilled and adaptable workforce capable of continuous improvement. However, there may be a shortage of workers with the necessary skills, and retraining existing employees can be time-consuming and expensive (Tiwari & Tiwari, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%